From the Far East to the Far West. Portuguese Discourse on Translation: A case study of Camilo Pessanha. (2nd January 2016) - Pinto, Marta Pacheco
Abstract : The history of translation is a site of memory that gathers testimonies of various kinds, from texts to images, from translated literature to statements reflecting on translation praxis. In Portugal, the existing anthologies of comments on translation into Portuguese are heavily dependent on a Eurocentric view of Portuguese literary and translation history, and rather neglect or elide the discourses of those who translate(d) lesser known literatures, particularly those written in non-Western languages, as is the case of Chinese and Japanese. The present article conceptualizes a project that seeks to put together a collection of meta-discourses by translation agents working with languages and textual traditions other than Western. The aim of such a project is to delocalize Portugal's history of translation by offering a corpus that testifies to the long-term cultural transfers between two geographical extremes: the Far East, which here refers exclusively to China and Japan, and the Far West, which is where I position Portugal from the viewpoint of the Far East. This anthology of texts about a Far Eastern geocultural periphery in translation would be an important bibliographical source for historical research necessary to (re)think, (re)write, and (re)map the Portuguese tradition of translation. The kinds of text to be anthologized are illustrated on the basis of a case study: the preface by the Portuguese symbolist poet Camilo Pessanha (1867–1926) to his direct translation from Chinese into Portuguese of eight elegies from the Ming Dynasty (1368–1644), which was published in Macau in 1914. The article is thus divided into three parts: the first part provides an historical overview of the translation flows between the Far West and the Far East; the second part sketches the structure of a representative anthology of voices translating from East Asian languages; and the third part analyses Pessanha's statements on his poetry translations and literariness of Chinese language.